Interaksyon: The online news portal of TV5 - Pitoc, Mark Raymond M. (Animo Repository, 2012)
Interaksyon.com is a growing brand known for its unparallel delivery of news online. It is a subsidiary of News 5, the news and information programming block of TV5 with its affiliate radio station, Radyo Singko 92.3 FM, and from various news wire services. Interaksyon.com was launched in the Philippines last February 2011 in pursuit of network’s stronghold mission: “Higit sa balita, Aksyon!” (More than News, Action!). The news website received numerous recognitions from prestigious award-giving bodies and admired institutions on its first year of operations. In spite of its achievements, Interaksyon.com is not yet at par with other news websites in the Philippines in terms of traffic rankings. The plan is to run the campaign for the whole year beginning on its second anniversary this February 2013. This campaign is created to drive brand awareness for Interaksyon.com in the country. Its main objective is to translate its world-class standards to a value that target customers here in the Philippines can relate to. The campaign uses several media outlets ranging from below the line, through the line, and above the line advertising. Feedback methods will be implemented after the initial phase of the campaign. Post-promo reports such as focus group discussions, online buzz metrics, and other market penetration data will be utilized to verify if targets were met.